A morphology-dependent lattice stability investigation in ZnS nanostructures by high-pressure XAFS studies. Issue 33 (3rd August 2022) - Dong, Qing; Li, Shujia; Liu, Ran; Liu, Bo; Li, Quanjun; Kim, Jaeyong; Liu, Bingbing
Abstract : High-pressure XAFS study reveals that the wurtzite ZnS nanorods directly transform into the rock salt phase, showing the high stability of nanorod morphology, which is attributed to its low-energy circumferential surface of ±(21̄0). Abstract : The morphology-dependent behavior of nanomaterials under high pressure has always been a research hotspot due to its great importance in the materials science and physical science fields. Here, we performed in situ high-pressure X-ray absorption fine structure (XAFS) measurements on wurtzite ZnS nanorods and nanoparticles. The XAFS signals show that wurtzite ZnS nanorods transform to the rock salt phase around 19–20 GPa without undergoing the transition to a zinc blende structure, consistent with the high-pressure XRD results. The fitting of the Zn–S bond length in the first shell manifests that the atoms in the ZnS nanorods are more challenging to compress than those in nanoparticles, and the nanorod-type wurtzite ZnS undergoes an abrupt lattice change when directly transitioning to the rock salt structure. The results reveal that the nanorod morphology presents high stability for wurtzite ZnS due to the low-energy circumferential surface of ±(21̄0). Our findings suggest that the nanorod is an ideal morphology for wurtzite ZnS in practical applications and will contribute to investigating the morphology effects on nanomaterials.